Pengaruh Konsentrasi dan Frekuensi Aplikasi Deltametrin terhadap Resurjensi Nilaparvata lugens - Yuni Ratna; Y. Andi Trisyono; Witjaksono Witjaksono; Didik Indradewa (Jurnal Perlindungan Tanaman Indonesia, 2010)
Nilaparvata lugens is the type of insect pest whose resurgence is induced by insecticides. Deltamethrin is an insecticide commonly used by farmers to control pests other than N. lugens on rice. This research was conducted to determine the effect of sublethal concentrations and application frequency of deltamethrin on subsequent growth and development of third instars of N. lugens. The selected concentrations were 50 ppm (LC25) and 225 ppm (LC50), and the frequency of applications ranged 1–3 times. Each concentration was applied to the third instars of the parent generation (one time), the parent and their first offspring (two times) and the parent, their first and second offspring (three times). N. lugens used in this experiment was the susceptible population derived from the laboratory population. Application of deltamethrin on two and three consecutive generations increased nymphal mortality, the population of offspring produced by the surviving adults, and the ratio of treated and control females in producing the offspring. Increasing the frequency of application increased the ratio, and the females received three applications produced nymphs 2.65 times more than the control females. The two sublethal concentrations did not have significant impact on the above parameters. Furthermore, the interaction between concentration and frequency of application was absent. These findings suggest that several applications of deltamethrin at sublethal concentrations would contribute to the resurgence of N. lugens.